Political parallelism in Iceland: Perceived media-politics relations - Guðmundsson Birgir (Nordicom Review, 2021)
My main objective in this article is to examine the importance of political parallelism in Iceland through establishing the extent to which political parallelism is perceived to char-acterise political communication in Iceland by politicians and voters. Political parallelism is one of the defining elements of Hallin and Mancini's typology of media systems. Based on candidate surveys from five elections and a voter survey, indexes of perceived political parallelism are configured for politicians and voters. The analysis suggests a high degree of perceived political parallelism and that the perceptions are reflected in partisan ideological views of individual media outlets. The same – or at least similar – perceptions about political parallelism in the media system seem to penetrate the system irrespective of age and at the national, local, and individual level of politics. However, voters and candidates of social democratic and liberal internationally oriented parties perceive a significantly lower degree of parallelism than others.